Light Interception and Productivity of Maize Intercropped With Legumes in Kharif Season - Naher, Q; Hossain, MA (Bangladesh Agronomy Journal, 2022)
The experiment was carried out at the Bangladesh Agricultural Research institute, Joydebpur, Gazipur during 2012 to evaluate the intercepted PAR in maize intercropped withlegumein comparison to monoculture for better weed suppression, productivity and economic benefits in kharif season. There were 17 treatments in the experiment viz., T1= Sole maize (no weeding), T2= Maize + Mungbean (no weeding), T3= Maize + Mungbean (weeding at 20 DAE), T4= Maize + Mungbean (weeding at 40 DAE), T5= Maize + Mungbean (weeding at 20 and 40 DAE), T6= Maize + Soybean (no weeding), T7= Maize + Soybean (weeding at 20 DAE), T8= Maize + Soybean (weeding at 40 DAE), T9= Maize + Soybean (weeding at 20 and 40 DAE), T10= Maize + Blackgram (no weeding), T11= Maize + Blackgram( weeding at 20 DAE), T12= Maize + Blackgram( weeding at 40 DAE), T13= Maize + Blackgram (weeding at 20 and 40 DAE) T14 =Sole maize (weed free), T15= Sole Mungbean (weed free), T16=Sole Soybean (weed free) and T17= Sole Blackgram (weed free).The results showed that PAR was significantly affected by cropping system, where it was higher in intercropping systems compared to sole crop . Regarding weed control, intercrops were more effective than sole crops and it was related to lower availability of PAR for weeds in intercropping systems. The highest grain yield (8.05 t ha-1). was obtained from weed free sole maize Among all intercropping, maize + mungbean along with two hand weeding gave the highest yield (maize: 7.18 t ha-1; 572.6 kg ha-1 mungbean), maize equivalent yield (MEY) = 12.49t ha-1and BCR = 2.84). From the study it can be concluded that maize mungbean intercropping with two hand weedings at 20 and 40 DAE would be the best in reducing weed growth, producing maximum yield and net return in intercropping systems under kharif season. Bangladesh Agron. J. 2021, 24(2): 137-149